THE EFFECT OF TEA PARTY STRATEGY TOWARDS STUDENTS’ READING COMPREHENSION - Karci Iva Ardiany; Eka Wilany (JETA (Journal of English Teaching and Applied Linguistic), 2021)
The objective of the study was to find out whether tea party strategy gave a significant effect towards students’ reading comprehension at the tenth grade of SMA Negeri 23 Batam in academic year 2019/2020. This research used a quantitative approach. In this research, experimental method was used as the method. The researcher focused on quasi experimental. The population was the students at the tenth grade students that consisted 0f 288 students that selected by using cluster sampling technique. The sample was two classes as experimental and control class. The researcher used quantitative data by giving pre-test and post-test to measure the students’ reading comprehension. The result of this research was the data gotten by giving pre-test and post-test. The result of calculating t-test was tcount < ttable (0.895 < 1.997), it means that Ho was accepted and Ha was rejected. Therefore, there was no significant effect of tea party strategy towards students’ reading comprehension at the tenth grade of SMA Negeri 23 Batam. However, Tea Party strategy could encourage the student more active in the learning process and it could create an enjoyable learning atmosphere. The tea party strategy could increase teamwork between students, could improve the students’ critical thinking, and could improve the students' confidence and students' interest in learning reading comprehension. Therefore, the teacher could carry out the tea party strategy in reading comprehension to improve the students’ reading comprehension.